Population dynamics of insect pests and some of their natural enemies and their correlation with weather parameters on Bt cotton - MUCHHADIYA, D V; SARADAVA, D A; KABARIA, B B (The Indian Journal of Agricultural Sciences, 2014)
The study was conducted at different villages of Rajkot district (Gujarat) to know the population dynamics and correlation of pests and their natural enemies on Bt cotton from 2008 to 2011. It revealed that sucking pests such as jassid, white fly, thrips, and aphid were found damaging the Bt cotton throughout the season however their peak activity was found on 39th SMW (3.50/3 leaves), 47th SMW (3.48/3 leaves), 38th SMW (2.94/3 leaves) and 51st SMW (27.23%), respectively. Mealy bug appeared from 33rd S M W and reached its peak on 50th SMW (1.95 grades). The peak period of bollworms, heliothis, spotted bollworm, pink bollworm and leaf eating caterpillar were 41st SMW (0.11/pl.), 39th SMW (0.08/pl.), 51st SMW (0.26/pl.) and 41st SMW (0.18/pl.), respectively. In natural enemies chrysopid was found higher in number than spiders and coccinellids throughout the season. The peak periods of the coccinellids, chrysopid and spiders were found on 42nd SMW (0.51/pl.), 45th SMW (3.01/pl.) and 32nd SMW (1.13/pl.), respectively. Correlation amongst sucking pests showed that jassid, whitefly, aphid and mealy bug population showed significant positive correlation with sunshine hours and significant negative association with rainfall whereas thrips showed significant negative correlation with sunshine hours. Amongst bollworms, heliothis, spotted bollworm and leaf eating caterpillar showed significant negative correlation with rainfall whereas spotted bollworm and spodoptera showed significant positive correlation with sunshine hours. Pink bollworm showed significant negative correlation with maximum and minimum temperature and morning and evening relative humidity. In natural enemies, chrysopid and coccinellid showed significant negative correlation with rainfall whereas spiders showed significant positive association with rainfall however chrysopid showed significant positive correlation with sunshine hours.